The battle of the fields : rural community and authority in Britain during the Second World War - Short, Brian, 1944- (The Boydell Press, 2014)
This book will appeal not only to historians and geographers, but to many who maintain a deep interest in the British countryside and its past, and to those who continue to share a fascination for the Second World War, in particular the 'home front'.